Paket Informasi Literasi Budaya di Perkampungan Nelayan Kampung Batu, Batang Arau, Padang Selatan, Kota Padang - Gusmanti, Novia; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis paper discusses the creation of a cultural literacy information package at Kampung Batu Fisheries Village, Batang Arau, Padang Selatan, Padang City. The purpose of this paper is to describe the process of creating a Cultural Literacy Information Package at Kampung Batu Fisheries Village, Batang Arau, Padang Selatan, Padang City. This research uses a descriptive method. Data was collected through literature review and direct observation and interviews with the Chairperson of RW, Fishermen and Community Leaders at Kampung Batu Fisheries Village, located in RW II, Batang Arau Sub-District, Padang Selatan District, Padang City. The information package is made through five stages. (1) Determining topics and types of packaging information packages, the topics raised were Cultural Literacy at Kampung Batu Fisheries Village, Batang Arau, Padang Selatan, Kota Padang; (2) Collection of information carried out by means of literature searches and interviews and direct observations to Kampung Batu Fisheries Village; (3) Analysis of the results of information gathering, it is known that things considered important as builders of the cultural identity of fishing communities such as gender systems, patron-client relations, patterns of resource exploitation, and social leadership; (4) Information packaging, carried out by presenting information that has been obtained from the collection of information in the form of information packages; (5) Evaluation of information packages carried out by submitting questionnaires to respondents and note that 92.4% of respondents strongly agree that information packages on cultural literacy are interesting, are informative and have use values.Keywords: information package; cultural literacy; fisherman